2016
DOI: 10.1007/s10973-016-5607-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of strontium-doped hydroxyapatite for biomedical applications

Abstract: The aim of this study was to investigate the effect of strontium (Sr) doping into hydroxyapatite (HA) powders. It is well known that strontium promotes bone formation, reduces bone resorption and it is used to treat osteoporotic diseases as stated previously by researchers. Strontium-doped HA (Sr-HA) was produced by precipitation with increasing amount of ion exchange between calcium (Ca) and Sr. Two different Sr amounts as 2 and 4 mol% were doped into HA by adding Sr(NO 3 ) 2 to the reaction solution. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…The mass loss up to 200 o C may be due to the evaporation of physically adsorbed water on the surface of particles of HAPs in good agreement with thermal analysis of related compounds [2,3,31,32]. The second mass loss from 200 to 800 o C may correspond to desorption of chemically bounded water to the HAPs lattice, which needs more energy to release that water from HAPs structure, as supported by DSC data (figs.…”
Section: Table 2 the Size Of Crystallites And Crystallinity Degree Fosupporting
confidence: 78%
See 3 more Smart Citations
“…The mass loss up to 200 o C may be due to the evaporation of physically adsorbed water on the surface of particles of HAPs in good agreement with thermal analysis of related compounds [2,3,31,32]. The second mass loss from 200 to 800 o C may correspond to desorption of chemically bounded water to the HAPs lattice, which needs more energy to release that water from HAPs structure, as supported by DSC data (figs.…”
Section: Table 2 the Size Of Crystallites And Crystallinity Degree Fosupporting
confidence: 78%
“…Certainly, water in pores requires more heating to be released due to the capillary effect. Thermal analysis at high temperature might be associated with the gradual loss of lattice water [2,3,21,[31][32][33][34]. Above 800 °C up to 1000 o C, the weight loss is insignificant and cannot be attributed to structural decomposition of HAPs biomaterials.…”
Section: Table 2 the Size Of Crystallites And Crystallinity Degree Fomentioning
confidence: 99%
See 2 more Smart Citations
“…Sr has been shown to stimulate bone formation and decrease bone resorption in both animal studies and clinical trials (Braux et al, ; Neves, Linhares, Costa, Ribeiro, & Barbosa, ). For these reasons, Sr‐substituted HA has attracted considerable interest from researchers and clinicians (Curran, Fleming, Towler, & Hampshire, ; Özbek, Bastan, & Üstel, ; Wong et al, ). It was reported that Sr 2+ can substitute Ca 2+ in a number of CaP phases, including ACP, HA, OCP, and brushite (Rokita, Hermes, Nolting, & Ryzcek, ).…”
Section: Introductionmentioning
confidence: 99%